What works in advocating for food advertising policy change across an english region - a realist evaluation - Susie Sykes; Megan Watkins; Matthew Bond; Catherine Jenkins; Jane Wills (BMC, 2023)
Abstract Background With increasing recognition of the role of commercial determinants of health, local areas in England have sought to restrict the advertising of products high in fat, salt and sugar (HFSS) on council-owned spaces, as part of wider strategies to reduce obesity. While there is some evidence of the impact of such policy change on behaviour, little is known about what works in the process of implementing this policy change. Methods Guided by a realist evaluation framework that explores the interaction between context, mechanism and outcomes, this study aims to investigate the factors that influence the restriction of outdoor advertising of HFSS products in one region in England. It refines a programme theory co-produced with stakeholders from 14 local authorities within a region and uses multiple data sources from each area with an in-depth examination of four case study sites. Data sources include longitudinal realist interviews, focus groups and surveys with policy advocates and policy stakeholders. Data were analysed retroductively to understand the causal link between context, mechanism and outcomes. Results Outcomes were driven by five dominant mechanisms: a strategic and staggered approach to stakeholder engagement, gathering intelligence, identifying policy champions, building relationships, reframing the issue; and two secondary mechanisms of amplifying the issue and increasing public will. These led to varied outcomes with no changes in formal policy position within the evaluation period but draft policy guidance in place and changes in political will demonstrated. Dominant context factors influencing change included having a named and resourced policy advocate in place supported by an external Community of Improvement and having existing aligned local objectives. Organisational complexity and change, financial concerns, lack of local examples, ideological positions and the pandemic were also influencing contextual factors. Conclusion Effecting policy change in this area requires the commitment of an extended period and the valuing of short-term policy outcomes, such as increasing political will. The importance of a resourced and well-supported policy advocate to lead this work is fundamental and the commercially sensitive nature of this policy change means that a complex interplay of mechanisms is required which may be dominated by a strategically staggered approach to stakeholder engagement.